1991
DOI: 10.1902/jop.1991.62.4.264
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evaluation of the Use of Decalcified Freeze‐Dried Bone Allograft With Guided Tissue Regeneration in the Treatment of Molar Furcation Invasions

Abstract: The purpose of this study is to evaluate the potential of decalcified freeze-dried bone allograft (DFDBA) combined with a barrier material in the treatment of human molar furcation defects (experimental) as compared to the barrier technique alone (control). Fifteen pairs of Class II or III furcation invasion defects comprised the study group. Measurements with calibrated periodontal probes were made to determine soft tissue recession, probing depth, and attachment levels. Defects from each pair were randomly s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
92
4
4

Year Published

1992
1992
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(111 citation statements)
references
References 11 publications
11
92
4
4
Order By: Relevance
“…GTR with either decalcified freeze-dried bone allograft (Anderegg et al, 1991) or composite grafts of autografts and tricalcium phosphate and/or demineralized freeze-dried bone allografts (Schallhorn and McClain, 1988) showed substantially more bone fill on re-entry in comparison with other studies (Wallace et al, 1994;Becker et al, 1995) which have shown no real benefit of the combination of GTR and grafting material. Caffesse et al (1993) reported results of treatment of furcation defects in beagle dogs, with and without demineralized freeze-dried cortical bone grafts, in a GTR procedure and found that the use of the guided tissue regeneration procedure resulted in an increase in connective tissue and alveolar bone regeneration, but that adjunctive bone grafting in itself did not appear to enhance regeneration.…”
Section: (B) Guided Tissue Regenerationmentioning
confidence: 86%
“…GTR with either decalcified freeze-dried bone allograft (Anderegg et al, 1991) or composite grafts of autografts and tricalcium phosphate and/or demineralized freeze-dried bone allografts (Schallhorn and McClain, 1988) showed substantially more bone fill on re-entry in comparison with other studies (Wallace et al, 1994;Becker et al, 1995) which have shown no real benefit of the combination of GTR and grafting material. Caffesse et al (1993) reported results of treatment of furcation defects in beagle dogs, with and without demineralized freeze-dried cortical bone grafts, in a GTR procedure and found that the use of the guided tissue regeneration procedure resulted in an increase in connective tissue and alveolar bone regeneration, but that adjunctive bone grafting in itself did not appear to enhance regeneration.…”
Section: (B) Guided Tissue Regenerationmentioning
confidence: 86%
“…The result is consistent with similar studies. 12,34,35 However, it should be pointed out that none of the treatment modalities resulted in complete closure of the Class II furcation defects. Some other studies have reported a similar result while using the GTR technique for the treatment of furcation defects.…”
Section: Discussionmentioning
confidence: 99%
“…However, Cortellini et al (37) reported that the depth of the infraosseous component of the defect is one of the most important factors in achieving the maximum regenerative potential. Anderegg et al (38) also reported that the deeper the vertical component, the greater the repair.…”
Section: Defect Morphologymentioning
confidence: 96%
“…Despite the limited number of trials evaluating the outcome of furcation therapy in conjunction with GTR and different filling materials, there seems to exist a trend for better horizontal resolution of furcation using combined therapy (2,3,7,38). The function of a grafting material in association with GTR would be as a scaffold to ensure clot stabilization and to provide and maintain space whenever the membrane may have the possibility to collapse, therefore, reducing the space for regeneration.…”
Section: Surgical Factors Influencing Successful Regenerationmentioning
confidence: 99%